2020
DOI: 10.1002/ece3.6801
|View full text |Cite
|
Sign up to set email alerts
|

Lizard predation by spiders: A review from the Neotropical and Andean regions

Abstract: Vertebrate predation by invertebrates has been classically underexplored and thus underestimated, despite the fact that many arthropods consume vertebrates. To shed some light on the relevance that spider predation may have upon lizards in the Neotropical and Andean regions, we compiled the available information in the literature on this trophic interaction. We found 50 reports of spiders consuming lizards in these regions, and the 88% of these were from the Neotropical region. Spiders belong to eight families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…The southern lizards also emitted fewer distress calls, which may be related to less predation risk, much as bird species with low predation risk emit fewer distress calls (Møller & Nielsen, 2010 ). Predation pressures experienced by populations of the Weeping lizard are not known, although based on data for other Liolaemus species, the southern population may have less predation pressure, at least from “non‐traditional” lizard predators (e.g., spiders, Reyes‐Olivares et al, 2020 ; passerine birds, Troncoso‐Palacios et al, 2020 ), because this kind of threat has been only reported to affect lizards in the northern and central portions of the Weeping lizard distribution. Furthermore, fewer calls of the southern population have ultrasonic components, which are likely to encode messages for predators rather than for conspecifics (see next section; Labra et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The southern lizards also emitted fewer distress calls, which may be related to less predation risk, much as bird species with low predation risk emit fewer distress calls (Møller & Nielsen, 2010 ). Predation pressures experienced by populations of the Weeping lizard are not known, although based on data for other Liolaemus species, the southern population may have less predation pressure, at least from “non‐traditional” lizard predators (e.g., spiders, Reyes‐Olivares et al, 2020 ; passerine birds, Troncoso‐Palacios et al, 2020 ), because this kind of threat has been only reported to affect lizards in the northern and central portions of the Weeping lizard distribution. Furthermore, fewer calls of the southern population have ultrasonic components, which are likely to encode messages for predators rather than for conspecifics (see next section; Labra et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used multi-species occupancy models to quantify patterns of site occupancy and detection for two small terrestrial frog species (Craugastor bransfordii and Oophaga pumilio) at La Selva Biological Station, and we modelled how frog occupancy and detection probability were influenced top-down by predatory spiders and bottom-up by resources (arthropod prey and leaf-litter microhabitat). Given the hypothesis that ctenid spiders are important predators of terrestrial frogs in the Neotropics (Menin et al 2005, Maffei et al 2010, Folt & Lapinski 2017, von May et al 2019, Nyffeler & Altig 2020, Reyes-Olivares et al 2020, Meneses et al 2021, we predicted that small terrestrial frogs would experience elevated occupancy in areas where predatory spiders are absent relative to where predators are present. To understand potential interactions between top-down and bottom-up factors, we also evaluated how top-down effects interacted with resources, by modelling how predator-prey interactions varied along a leaf-litter resource gradient.…”
Section: Introductionmentioning
confidence: 93%
“…The latter study observed a strong pulse in metamorphosis of frogs and hypothesised that this synchronous emergence may have evolved as a mechanism to satiate terrestrial spider predators (Donnelly & Guyer 1994, Guyer & Donnelly 2005. Recent studies from Central and South America have also found that ctenids are opportunistic predators of small vertebrates (Menin et al 2005, Maffei et al 2010, Nyffeler & Altig 2020, Reyes-Olivares et al 2020, Meneses et al 2021, and the accumulating literature suggests that spiders may play an important role as vertebrate predators across Neotropical wet forests (Hayes 1983, Guyer 1988, Donnelly & Guyer 1994, Menin et al 2005). However, no study has examined the extent to which ctenid spiders influence terrestrial frogs or other small vertebrates in a top-down, predator-prey context.…”
Section: Introductionmentioning
confidence: 99%
“…Investigaciones recientes han contribuido al conocimiento de la biología de G. rosea Reyes-Olivares et al 2020), sin embargo, no se ha documentado la dispersión de juveniles de esta especie. Como este es un evento raro, difícil de documentar y predecir (Shillington y McEwen 2006), los datos obtenidos en terreno fueron complementados con registros extraídos de diversos programas de ciencia ciudadana que usan las redes sociales para documentar la biodiversidad de los ecosistemas chilenos.…”
unclassified